2003
DOI: 10.3346/jkms.2003.18.1.53
|View full text |Cite
|
Sign up to set email alerts
|

No Changing Trends in Incidence of Gastric Cardia Cancer in Korea

Abstract: Although there is a controversy, several reports have shown that gastric cardia cancer has tended upwards in recent years. The aim of this study was to investigate the changing trend of stomach cancer according to the location of cancer and histologic type in Korea, where is known to be one of the most prevalent areas for gastric cancer. All the patients newly diagnosed as gastric cancer from 1991 through 2000 were recruited in Hallym University Medical Center. The periods were divided into the first (1991 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 28 publications
4
25
1
Order By: Relevance
“…Because there are a few western pattern of topography of gastric cancer, thus the trend overall might be reverse. In some other studies, mostly from Asia, the trend is similar to our study and there is no trend of migration to cardia, maybe due to traditional eastern nutritional habits (Lee et al, 2003;Makhdoomi et al, 2005). One possible interpretation for this migration is a studies.…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gassupporting
confidence: 89%
“…Because there are a few western pattern of topography of gastric cancer, thus the trend overall might be reverse. In some other studies, mostly from Asia, the trend is similar to our study and there is no trend of migration to cardia, maybe due to traditional eastern nutritional habits (Lee et al, 2003;Makhdoomi et al, 2005). One possible interpretation for this migration is a studies.…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gassupporting
confidence: 89%
“…First, because our analysis was retrospective, nonrandomized, and conducted at a single center, potential selection bias and referral bias cannot be excluded. Another possible limitation is that the number of patients included in each group was small because of the relatively low incidence of cardia cancer in Korea [3,4]. Although none of the patients in the surgery group had lymph node metastasis in this study, the possibility of lymph node metastasis cannot be completely excluded because of the limited sample size.…”
Section: Data Represent the Number Of Patients (%) Or The Median (Intmentioning
confidence: 91%
“…In contrast, studies on the incidence of EGJ adenocarcinoma have found no evidence of changing trends in Korea [3,4]. EGJ adenocarcinoma has a different etiology and clinicopathological features compared to distal gastric carcinoma.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, in Europe and the US, EGJ tumors represent about one-third of all esophagogastric adenocarcinomas [1,2], whereas this proportion does not exceed 10% in Far Eastern countries [3,4]. The different epidemiological trends seen for EGJ adenocarcinomas in different regions around the world reflect the geographical distributions of risk factors associated with EGJ, which are mainly related to the environment and lifestyle habits.…”
Section: Introductionmentioning
confidence: 99%